2017
DOI: 10.1093/jjco/hyx150
|View full text |Cite
|
Sign up to set email alerts
|

Facial flushing after alcohol intake as a predictor for a high risk of synchronous or metachronous cancer of the upper gastrointestinal tract

Abstract: A simple interview on history of facial flushing after alcohol intake can be useful for identifying patients at high risk for synchronous or metachronous cancers of the UGI tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Alcohol [12, 16, 2225], cigarette smoke [12, 16, 24], and alcohol metabolizing enzyme deficiencies such as aldehyde dehydrogenase-2 (ALDH2) [12, 26] are the main risk factors for HNC and esophageal cancer. Enzyme deficiencies as well as duration and density of exposure to alcohol and cigarette smoke may determine the risk of these cancers [12, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol [12, 16, 2225], cigarette smoke [12, 16, 24], and alcohol metabolizing enzyme deficiencies such as aldehyde dehydrogenase-2 (ALDH2) [12, 26] are the main risk factors for HNC and esophageal cancer. Enzyme deficiencies as well as duration and density of exposure to alcohol and cigarette smoke may determine the risk of these cancers [12, 24].…”
Section: Discussionmentioning
confidence: 99%
“…However, fewer studies have analyzed the risk factors for metachronous ESCNs. In a retrospective study, Harada et al found that only facial flush after drinking, but not smoking or drinking, was a risk factor for synchronous and metachronous gastrointestinal tract cancers, but the metachronous cancers included oral, oropharyngeal, hypopharyngeal, esophageal, and gastric cancers [14]. Fukuhara et al retrospectively analyzed 135 patients with primary HNSCC and found that multiple LVLs were significantly associated with the development of metachronous ESCC [10].…”
Section: Discussionmentioning
confidence: 99%
“…Hence a typical pint of beer at 4.5% ABV contains 2.5 units, a standard glass of wine (175ml) at 13.5%ABVis 2.3 units and a measure of whisky (25ml) at 40%ABV is 1 unit). In the Netherlands, it is 9.9 g. In France and Ireland, 10 g, in the USA it is 14 g and in Japan 22 g 4 . When comparing data between countries because of the variability in what constitutes a unit of alcohol, Tramacere et al converted the alcohol consumed into grams of alcohol using the following formula: 0.8g/ml=28.35 g/ounce= 12.5 g/ drink 5 .…”
Section: Introductionmentioning
confidence: 93%